Gold nanoparticle based optical and electrochemical sensing of dopamine - Yusoff, N.; Pandikumar, A.; Ramaraj, R.; Lim, H.N.; Huang, N.M. (Springer Verlag (Germany), 2015)
This review (with 110 refs.) gives an overview on the progress that has been made in the past few years on the use of gold nanoparticles (AuNPs) for use in sensors and analytical tools for the determination of dopamine (DA). Both AuNPs and their composites with other organic and inorganic materials including noble metals are treated. Following an overview on the clinical significance of DA, we discuss the various analytical methods that are (a) electrochemiluminescence (ECL); (b) surface enhanced Raman scattering (SERS); (c) colorimetric probing and visual detection; and (d) the large class of electrochemical sensors. Subsections cover sensors based on plain AuNPs, bimetallic NPs, AuNP-metal@metal oxide nanocomposites, AuNP nanocomposites with organic polymers, AuNP nanocomposites with carbon nanotubes or with graphene, and finally sensors based on ternary materials containing AuNPs. The review ends with a conclusion on current challenges of sensors for DA and an outlook on future trends.